Reforma szkolna z roku 2016 – troska o ucznia czy innowacja na zamówienie polityczne - Rondalska, Dorota (Studia Edukacyjne, 2017)
This article is devoted to the school reform of December 2016. The author discusses its appropriateness, the way it is introduced, and the social climate that accompanies it. This reform re-introduces the state from before 1998, i.e. an 8-year-long primary school and eliminates the junior school. The author raises a question about the justification for the reform, assuming that it does not take into account the results of the study on the effects of the 1999 reform, but may be politically-motivated. Another thesis concerns the repetition of the application errors of the previous reform as well as the formal way of introducing changes into the school system, especially the school network. The author points to a great social resistance against the reform, especially the way it is conducted and predicts that due to the hasty implementation of the reform and application errors, its effects may be half-hearted.